The Aesthetic group gymnastics, a new model of competition - Conesa, E.; Martínez Gallego, F. Mª. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2015)
The purpose of this study is to review the literature on the historical origins, the technical characteristics and the key aspects of the regulation of a new and relatively unknown sport; the Aesthetic Group Gymnastics (GEG). This sport, which origin is in the Nordic countries, especially Finland and Sweden in the 18th century, serves the society to especially encourage women to physical activity and maintain it over time. This call is still in force, and for about 10 years was introduced in our country and there is a considerable increase in the practice of the same among the female children and adolescents. This sport is implanted in Spain in response to the strict requirements of the International Regulations that gives priority to the health aspects. The GEG is defined as a sport based on the stylized and natural body movement, which combines and enhances qualities like dynamism, rhythm and harmony of movements performed with economic and natural use of force. It is an expression, art and feeling become competitive sport. All of this done by a group of athletes flowing aesthetic and synchronized movement. We analyse the technique and the most important characteristics of this sport that allows to understand the differences between itself and the rhythmic gymnastics.